The flavonoid luteolin, but not luteolin-7-o-glucoside, prevents a transthyretin mediated toxic response. - Iakovleva, I.; Begum, A.; Pokrzywa, M.; Walfridsson, M.; Sauer-Eriksson, A.E.; Olofsson, A. (PLoS ONE, 2015)
Transthyretin (TTR) is a homotetrameric plasma protein with amyloidogenic properties that has been linked to the development of familial amyloidotic polyneuropathy (FAP), familial amyloidotic cardiomyopathy, and senile systemic amyloidosis. The in vivo role of TTR is associated with transport of thyroxine hormone T4 and retinol-binding protein. Loss of the tetrameric integrity of TTR is a rate-limiting step in the process of TTR amyloid formation, and ligands with the ability to bind within the thyroxin binding site (TBS) can stabilize the tetramer, a feature that is currently used as a therapeutic approach for FAP. Several different flavonoids have recently been identified that impair amyloid formation. The flavonoid luteolin shows therapeutic potential with low incidence of unwanted side effects. In this work, we show that luteolin effectively attenuates the cytotoxic response to TTR in cultured neuronal cells and rescues the phenotype of a Drosophila melanogaster model of FAP. The plant-derived luteolin analogue cynaroside has a glucoside group in position 7 of the flavone A-ring and as opposed to luteolin is unable to stabilize TTR tetramers and thus prevents a cytotoxic effect. We generated high-resolution crystal-structures of both TTR wild type and the amyloidogenic mutant V30M in complex with luteolin. The results show that the A-ring of luteolin, in contrast to what was previously suggested, is buried within the TBS, consequently explaining the lack of activity from cynaroside. The flavonoids represent an interesting group of drug candidates for TTR amyloidosis. The present investigation shows the potential of luteolin as a stabilizer of TTR in vivo. We also show an alternative orientation of luteolin within the TBS which could represent a general mode of binding of flavonoids to TTR and is of importance concerning the future design of tetramer stabilizing drugs.